Labor Market Integration of People with Disabilities According to Polish and Greek Legislation - Dorota Kobus-Ostrowska; Doxa Papakonstantinou (Comparative Economic Research. Central and Eastern Europe, 2020)
The paper presents the types of support available to employers who employ individuals with disabilities, as well as opportunities for the disabled to enter the labor market, start a business, and keep it running. The text is enriched with information about the labor rights of people with disabilities. A thorough examination of the legislation in force in Poland and Greece led us to numerous and interesting conclusions. Despite many seemingly attractive forms of support available to employers and people with disabilities, we note that the labor participation rate of people with disabilities is still much lower in Poland and Greece than in many other European countries. What is the main barrier to the activation of people with disabilities? Although the answer to this question is certainly multi-threaded, it seems justifiable to claim that the complexity of the legislation, a number of stipulations in the area of public aid, and possible new adverse amendments to labor laws effectively discourage employers from creating jobs for people with disabilities and they discourage people with disabilities from being economically activated.
Keywords: J14; J64; J71; 330; people with disabilities; support; employer; labor market; Poland; Greece